STRAINS INJURY MANAGEMENT IN ATHLETICS MIDDLE DISTANCE RUNNING NUMBER - Indah Swira Sitanggang; Nur Hayati Simatupang; Cindy Vini Rosen Sipayung; Alpina Damayanti; Tarisa Aulia (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Strain injury is a physical condition where there is a tear or strain in the muscles and tendons which causes the tendons or muscles to stretch excessively. In sports, injuries often occur, such as strain injuries that often occur in middle-distance or 5000-meter athletes. In dealing with this injury, an athlete, coach and also the athlete's parents should get education about handling hamstring injuries in athletes. This study used the narrative literature review method. Based on the analysis of the article, the researcher obtained articles including, the span of the article publication within a period of 12 years. From the 10 journals studied and analyzed above, it can be concluded that the prevention and treatment of hamstring injuries requires a comprehensive approach, both through education and physiotherapy.